Management of gillnet bycatch of cetaceans in New Zealand - Dawson , Stephen M.; Slooten , Elisabeth (J. Cetacean Res. Manage., 2023)
Bycatch of dolphins in inshore gillnets first attracted scientific and management attention in New Zealand in the 1980s. During 1984-88, 50-150 dusky dolphins were killed each year at Kaikoura in gillnets set at the surface to catch bait for rock lobster. At the same time, annual catches of 20-100 Hector’s dolphins occurred in Canterbury waters in bottom-set commercial and recreational gillnets. These catches resulted in the banning of surface-set gillnetting at Kaikoura in 1989 and in the creation of the Banks Peninsula Marine Mammal Sanctuary in 1988 to protect Hector’s dolphin. An additional gillnet closure was established to protect North Island Hector’s dolphin in 2003. A key problem is that current information on catches in these and other areas is scant. One observer programme has been successfully implemented in a commercial gillnet fishery (Canterbury area, 1997/98 fishing season). Its estimate of Hector’s dolphin bycatch (17) is clearly unsustainable by the local population. Pingers have been voluntarily used in these fisheries, but there are no data establishing their effectiveness, and it has not been possible to ensure consistency of pinger use. There are no reliable estimates of numbers taken in recreational fisheries. Area closures are used to mitigate gillnet bycatch of Hector’s dolphin, however it appears that the Banks Peninsula Marine Mammal Sanctuary is not large enough to ensure the persistence of the Canterbury population. There is a bycatch limit in place for this population, although it is unenforced. We argue that management of this species via bycatch limits is not practical, however. Hector’s dolphin’s low abundance and separation into several distinct populations means that appropriate bycatch limits would be very small, and this necessitates very comprehensive observer coverage to be confident they are not exceeded. We propose that increasing the size of protected areas is the most reliable option for conservation.